Factors affecting the distribution of teachers of the first cycle from the point of view of mentors in the Directorate of Education of Lattakia - غانم , ثناء; عبد الرحمن, نسرين; أسود , رباب (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research aims to identify the factors affecting the distribution of teachers, how to deal with these factors, and to identify the obstacles that hinder the distribution of teachers, and the mechanism for dealing with these obstacles. By conducting interviews with a sample of (27) educational supervisors in the Lattakia Education Directorate, the descriptive approach was used, and the following results were reached: The most important factors that affect the distribution of teachers from the point of view of the mentors, the needs of the educational areas, health conditions, and teachers' housing. There is a difference in the opinions of mentors regarding the steps of the human resource planning process, which requires holding training courses on planning processes for the distribution of teachers and how to make optimal use of human resources according to their answers to the corresponding research tool questions.